Structural Dynamic Analysis of Endogenous Vibration of Large-span Plant at Datengxia Hydro Project - LI Shuai; XIE Ji'an (Renmin Zhujiang)
The vibration energy generated by the internal source vibration during the operation of the power plant room is very large,which will endanger the safety of the building and the health of the operating personnel when serious.So the endogenous vibration characteristics of the plant as a whole and important individual structures were carried out based on finite element calculation theory,and the vibration response of the power plant house under unit vibration load and flow channel pulsation pressure was calculated.The results show that the natural vibration frequency of the whole plant and the important single structure and the main vibration source of the unit have enough stagger,under the vibration load of the unit or the pulsating pressure of the flow passage.The vibration displacement,velocity and acceleration response amplitudes of the workshop structure meet the control standard under the vibration load of the unit or the pulsating pressure of the flow passage.In summary,the effect of endogenous vibration loads at different frequencies in the Datengxia Hydro Project will not adversely affect the safe operation of the powerhouse.